Early childhood teachers’ awareness of psychomotricity (Olhar de Professor, 2020)
The present study has the purpose of investigating teachers from a public school in the North of Parana’s awareness of the importance of psychomotricity in children’s learning process and its’ understanding. The data were collected with a questionnaire with two open-ended questions to find out what is known about psychomotricity and its’ relation with learning and children’s learning difficulties, according to the participating teachers. The results indicated that the concept of psychomotricity is well-understood among the participants, but there is little knowledge about the connection between learning and practicing psychomotor skills as a means of preventing leaning difficulties.
Keywords: Psychomotricity. Early childhood education. Learning difficulty.